ANALISIS KONDISI SOSIAL EKONOMI MASYARAKAT SEKITAR KAWASAN HUTAN KOA (Studi Kasus Desa Linamnutu, Kecamatan Amanuban Selatan, Kabupaten Timor Tengah Selatan) - Heni D A'oetpah; Mamie E Pelondo'u; Nixon Rammang (Wana Lestari, 2021)
The Koa Forest Area is a protected forest area which is administratively located in South Central Timor Regency with two villages as the main supporters, namely Mio Village and Linamnutu Village. The purpose of this study was to determine the socio-economic conditions of the community around the Koa Forest area, in Linamnutu Village, South Amanuban District. This research was conducted for 2 months, starting from October 2019 to November 2019. Data collection was conducted by observation, interviews and literature study. All data that has been collected are edited to improve data quality and tabulated models are made then analyzed descriptively. The results showed that socio-economically most of the residents of Linamnutu Village in the vicinity of the Koa Forest area have a main livelihood as farmers, have a low level of education, are modest and use forest products to meet their daily needs. The existence of the Koa Forest area has an important role for the people of Linamnutu Village, seen from the level of community dependence on the Koa Forest area, which is 72.3%. The people of Linamnutu Village make use of various forest products such as Asam (Tamarindus Indica), Gewang (Coripha Utan Lamk), Bamboo (Bambuseae), firewood and Kaikena seeds. Economically, the average income of the people of Linamnutu Village is IDR 1,136,782 / month and the total monthly household expenditure ranges from IDR 350,000 / month - IDR 2,100,000 / month on average. expenditure of 952,299, - / month while the average household net income was 191,379, - / month.